THE ROLE OF TRUST IN MEDIATING THE INFLUENCE OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON REPURCHASE INTENTION IN ONLINE TRADING APPLICATIONS IN DENPASAR - Pramitha, Intan (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study aims to analyze the effects of perceived usefulness and perceived ease of use on repurchase intention, with trust acting as a mediating variable, in the context of online trading applications in Denpasar. The research adopts a quantitative approach, utilizing Partial Least Squares (PLS) for data analysis. The findings indicate that both perceived usefulness and perceived ease of use significantly influence repurchase intention. These factors enhance user trust, which in turn encourages users to repurchase via online trading applications. The results suggest that online trading platforms should focus on improving the perceived usefulness and ease of use of their applications, as well as building customer trust to increase user loyalty and repurchase intention. This research contributes valuable insights for developing marketing strategies and managing customer relationships in the financial technology sector, particularly for online trading applications.